Factors That Affect Employee Effectiveness and Efficiency at PT. XYZ - Fahmi Hidayat (Institute of Computer Science (IOCS), 2019)
To enforce discipline is not enough just with threats, but it needs to be balanced, namely a sufficient level of welfare. Even so, actually discipline is not only determined by factors of well-being, but there are still many other factors, also need continuous habits. Based on preliminary research conducted at PT. Xyz, then the problem faced can be formulated as follows